A NOVEL STRAIN OF SHIGELLA SPECIES OUTBREAK IN A RESIDENTIAL SCHOOL IN PEMAGATSHEL, BHUTAN, 2012 - Tsheten, Tsheten; Tshering, Dorji; Gyem, Kinley; Dorji, Sangay; Wangchuk, Sonam; Irfani, Tri Hari; Letho, Letho (Public Health of Indonesia, 2016)
Background: A cluster of suspected shigellosis was reported from health center in Pemagatshel district to Royal Center for Disease Control on 14th May 2012. The investigation was done to determine the cause and risk factor for the outbreak so that appropriate control and prevention measures can be implemented.Methods: A descriptive study was used for the outbreak investigation. The food items and drinks served to boarding students were collected from the mess in-charge in order to assess their risk for the outbreak. The kitchen and its premises were inspected to study the likely contamination by rodents and other animals. The water and stool specimens were tested in the laboratory to identify all possible enteric pathogens.Results: 82 boarding students were affected with an overall attack rate of 28% (82/294). Diarrhea was the predominant symptom followed by abdominal pain and headache. The onset date of the cases varied between 11th and 18th May, 2012. Shigella species was isolated from stool specimens that showed resistant to amoxicillin, nalidixic acid, chloramphenicol and sulfamethoxazole. Water specimen collected from source, distribution reservoir and tap water at school were found grossly contaminated.Conclusion: The outbreak was caused by novel strain of Shigella species which was not detected earlier in Bhutan. The promotion and provision of boiled water will greatly reduce the incidence of shigellosis especially in boarding facility.